The Efficacy of Coenzyme Q10 for Improving Vigilance - Jirattitikarntavorn, Napat; วงศ์ศุภสวัสดิ์ กานต์ (Rattanakosin Journal of Science and Technology, 2022)
Dementia is a major problem that occurs in an increasing number of populations with a faster aging process. The first symptom that causes it is a loss of awareness and vigilance, which leads to cognitive decline, leading to dementia. The objective of this study was to study the efficacy of Coenzyme Q10 by taking a supplement containing 200 mg of Coenzyme Q10 daily for 8 weeks to improve awareness and vigilance. This study was an experimental study in 31 female subjects, aged 40 to 60 years without mild cognitive impairment (MCI), divided in 2 groups. Experimental group contained 15 subjects taking Coenzyme Q10 extract and controlled group contained 16 subjects taking placebo. This study used the Trail Making Test A and the Modified Mackworth Clock Test to measure reaction time and accuracy rate at the beginning of the study and at 4 and 8 weeks. In this study, the 8-week improvement in measurement accuracy was improved in both groups from the learning curve, but there was no significant difference between the two groups (p>0.05) at each time interval. For the measure of response time, there was no significant reduction (p>0.05) in either group, and no significant difference between the two groups (p>0.05) at each time point. Therefore, it was concluded that coenzyme Q10 intake in females aged 40-60 years without dementia did not improve awareness and vigilance.